EARTHWORM Vermiculture and Vermi Composting - R.k.Bhatnagar; R.K.Palta (Ludhiana Kalyani, 1996)
Earthworms of world are classified in to 10,families, comprising 240 genera and about 3320 species.
Role of Earthworms Organic wastes Vermiculture Vermicomposting
Keywords: Role of Earthworms ,Organic wastes ,Vermiculture